Morphological and GIS-based land use Analysis: A Critical Exploration of a Rural Neighborhood - Oluwagbemiga Paul Agboola; Mohd Hisyam Rasidi; Ismail Said; Samson Olutayo Abogan; Adebambo Stephen Adejuwon (Journal of Contemporary Urban Affairs, 2018)
The significance of neighbourhood in hosting a group of dwellings units and possessing adequate communal facilities could not be overemphasized in the study of people and place relationships. There are two main objectives of this study: (i) to study the neighbourhood’s associated challenges through the size, growth, and land use distribution, and (ii) to investigate the perceived inhabitants’ activities pattern within the neighbourhood. The objectives are explored through a morphological and GIS-based land use analysis of a rural neighbourhood in South-west, Nigeria. The town is studied in three transformation phases, dating back to five decades using ArcGIS version 10.3. The 1st phase spanned between the year 1910 to 1959, while the 2nd and 3rd phases ran through the year 1960 to 1999, and the year 2000 to 2015 respectively. The exploration in this study is to document the diverse neighbourhood challenges, features, and prospects, which remain uninvestigated in the case study area for the past years. In conclusion, human historical and social influences play a significant role in ameliorating the challenges associated with the spatial developments of the settlements. The implication of the study becomes vital to the major stakeholders and professionals in the built environment on the significance of enhancing the sustainable communities in Nigeria.